Choroid Plexus Papilloma in a Bitch - Richeli Kuwer, Kátia; Oliveira Chaves, Rafael; Copat, Bruna; Oliveira Vasques, William; Sonne, Luciana; Conceição de Oliveira, Eduardo (Acta Scientiae Veterinariae, 2022)
Background: Choroid plexus papilloma is a benign neoplasm derived from the neuroepithelium of the choroid plexus of the ventricular cavity, commonly located in the fourth ventricle, affecting dogs of different age groups and without predilection for sex. There is a range of therapeutic options, and the treatment to be chosen will be defined based on tumor localization and development. Due to the difficulties in accessing treatments, tutors opt for euthanasia or death occurs with the worsening of the clinical condition. This case report aims to present the symptomatology, treatment and evolution of the case until the death of the animal, as well as the pathological findings. Case: A 12-year-old bitch, mixed breed, was treated presenting behavior alteration, with unusual aggressiveness, perceived by the tutor four weeks ago. Neurological examination revealed changes in behavior, compulsive walking and focal epileptic seizures. After the presumptive diagnosis of brain neoplasia, the dog underwent symptomatic treatment with prednisolone (1 mg/kg, orally, every 24 h, for 15 days, with subsequent reduction to 0.5 mg/kg for another 15 days) and phenobarbital (3 mg/kg, every 12 h, orally), until death. After the beginning of the treatment, no more epileptic seizures and aggressive behavior were observed. After 5 months of consultation, the dog returned with aggressive and anorexic behavior. Due to the worsening of clinical signs, with the possibility of brain neoplasia, the tutor opted for euthanasia. Necropsy was performed and macroscopic examination was observed in the telecephalus, occlusion of the third ventricle by grayish mass, soft, 1.2 cm in diameter with slight dilation of lateral ventricles. On histological examination, it was observed that the third ventricle was occluded, epithelial proliferation of arboriform aspect, composed of cuboidal cells to columnares sustained by moderate fibrovascular stroma. Based on macroscopic and histopathological findings of the telecephalus, the alterations determined the diagnosis of choroid plexus papilloma. Discussion: The diagnosis of choroid plexus papilloma was confirmed by observing the neurological signs and pathological findings that characterize this neoplasm. Choroid plexus tumors are less common, in the third ventricle, only in 36% of all reports are of tumors in that area. The search for care is mainly due to clinical signs that include behavioral, and locomotor changes and sometimes epileptic seizures, such clinical signs were found in the dog. Choroid plexus papilloma affects dogs of all ages, but more in adults and increasing the occurrence as they age. The tumor is still correlated in a higher occurrence in large animals, the evaluated dog was of age, but small in size. During anamnesis, in addition to the clinical history, neurological examinations provide a good basis for the presumptive diagnosis that can be complemented by an imaging diagnosis. Sometimes such technologies are not available for use, therefore, more comprehensive knowledge about clinical signs and anamnesis are indispensable for a correct diagnosis. Palliative drug therapies are an excellent option for most cases presented in the literature and clinical routine, since they provide better quality of life by decreasing or eliminating clinical signs, besides being easily administered by tutors. The therapy proved to be of great value for the improvement of the clinical signs of the evaluated dog, confirming the importance of knowledge of the appropriate prescriptions for each case and reinforcing that consultation with one was important in defining the diagnosis and symptomatic treatment. Keywords: dog, neurology, tumor, benign, choroid plexus. Título: Papiloma de plexo coronoide em uma cadela. Descritores: cão, neurologia, tumor, benigno, plexo coroide.